2015
DOI: 10.1128/jvi.00559-15
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of Poly(ADP-Ribose) Polymerase 1 by a Viral Processivity Factor Facilitates Lytic Replication of Gammaherpesvirus

Abstract: In Kaposi's sarcoma-associated herpesvirus (KSHV), poly(ADP-ribose) polymerase 1 (PARP-1) acts as an inhibitor of lytic replication. Here, we demonstrate that KSHV downregulated PARP-1 upon reactivation. The viral processivity factor of KSHV (PF-8) interacted with PARP-1 and was sufficient to degrade PARP-1 in a proteasome-dependent manner; this effect was conserved in murine gammaherpesvirus 68. PF-8 knockdown in KSHV-infected cells resulted in reduced lytic replication upon reactivation with increased levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…In KSHV, PARP1 interacts with and PARylates Rta to repress Rta-mediated transactivation (Gwack et al, 2003). A recent study identified a KSHV protein that interacts with PARP1, targeting it for proteasomal degradation, and thus reducing levels of inhibitory PARylated-Rta (Cheong et al, 2015). Here, we identify a similar restrictive function for PARP1 in EBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In KSHV, PARP1 interacts with and PARylates Rta to repress Rta-mediated transactivation (Gwack et al, 2003). A recent study identified a KSHV protein that interacts with PARP1, targeting it for proteasomal degradation, and thus reducing levels of inhibitory PARylated-Rta (Cheong et al, 2015). Here, we identify a similar restrictive function for PARP1 in EBV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a body of evidence suggests that PARP1 may serve as a stress sensor—a function that would be especially relevant in regulating herpesvirus lytic reactivation (Mattiussi et al, 2007; Luo and Kraus, 2012). Reports in KSHV have shown that PARP1 is selectively downregulated by a lytic protein, and restricts KSHV lytic replication through various mechanisms, including poly(ADP-ribosyl)ation (PARylation) of the immediate early protein, Rta (Cheong et al, 2015; Gwack et al, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the processivity factor of KSHV and γHV-68, PF-8, binds to and targets PARP1 for degradation, which reduces PARylated RTA and enhances virus replication ( Fig. 4C; Noh et al 2012;Chung et al 2015). In contrast to the antiviral effects of PARPs during γ-herpesvirus infection, PARP activity seems to promote the replication of HSV-1, the prototype α-herpesvirus.…”
Section: Some Virus Families Encode For a Macrodomain Protein That Rementioning
confidence: 99%
“…Noteworthy, S. pyogens releases a NAD + glycohydrolase into the host cell that reduces PARP-1 activation and accumulation of PAR and interferes with inflammatory cytokine signaling and HMGB1 release [58]. PARP-1 and HMGB1 are also targeted by other pathogens such as gammaherpesviruses [59] and Chlamydia trachomatis [60] as a strategy to limit inflammation and evade immune response.…”
Section: Parp-1 and Its Pro-inflammatory Rolementioning
confidence: 99%